2010
DOI: 10.1007/s12032-010-9734-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic HuR expression correlates with angiogenesis, lymphangiogenesis, and poor outcome in lung cancer

Abstract: HuR is a ubiquitously expressed RNA-binding protein that stabilizes the mRNAs of certain genes and regulates the translation to proteins. Elevated cytoplasmic expression of HuR has been suggested to be associated with reduced survival in a wide variety of human carcinomas. However, the clinical significance of HuR expression in lung cancer remains unknown. In this study, we examined HuR expression in 132 patients with non-small cell lung carcinoma (NSCLC) by means of immunohistochemistry and correlated clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 34 publications
2
46
1
Order By: Relevance
“…Our results support former situation in patients with bladder cancer. As a mechanism underlying such pathological activities of HuR, regulation of angiogenesis has been suggested in various cancers [3], [4]. Special attention was paid to the relationships between HuR expression, malignant potential and pathological features because stimulation of angiogenesis has been linked to tumor growth and progression in patients with several malignancies, including bladder cancer [13], [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support former situation in patients with bladder cancer. As a mechanism underlying such pathological activities of HuR, regulation of angiogenesis has been suggested in various cancers [3], [4]. Special attention was paid to the relationships between HuR expression, malignant potential and pathological features because stimulation of angiogenesis has been linked to tumor growth and progression in patients with several malignancies, including bladder cancer [13], [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HuR has been found to be involved in the regulation of angiogenesis by interacting with the transcripts of numerous angiogenesis-promoting factors, and is also known to correlate with lymphangiogenesis in a variety of pathological conditions, including cancer [3], [4]. Based on these facts, it has been suggested that HuR plays important roles in carcinogenesis, tumor growth, metastasis, and prognosis in malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In lung cancer, several teams reported significant cytoplasmic HuR overexpressions in the cancer tissues, with an impact on the prognosis of the disease. In a series of 132 NSCLC, Wang et al found that cytoplasmic expression of HuR was an independent prognostic factor for survival in multivariate analysis [24,25]. Similarly, Lauriola et al showed, in 54 lung adenocarcinomas of stage I and II, an unfavorable independent prognostic value of the cytoplasmic, but not the nuclear expression of HuR [22].…”
Section: Hur Is Overexpressed In Lung Cancermentioning
confidence: 99%
“…In lung cancer, several studies have reported the prognostic value of cytoplasmic HuR [22][23][24][25][26]. If most of the evidence associates cytoplasmic HuR to cancer proliferation, the unfavorable prognostic value of nuclear HuR has, on the other hand, been demonstrated in ovarian [27] and colo-rectal carcinomas [28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on studies with individual mRNAs, HuR has been initially implicated in regulating alternative pre-mRNA splicing and cleavage/polyadenylation events [13,21,42,57,58]. At a transcriptome-wide level, the recently applied combined methods of PAR-CLIP and RIP-Chip assays unraveled a surprisingly large number of RNA-HuR interactions occurring in introns (1/3 of all associations) with many of them in the proximity of 3â€Č splice sites [22,41,42].…”
Section: Discussionmentioning
confidence: 99%